Diode-pumped, actively Q-switched Nd,La:CaNb2O6 self-Raman laser at 1,174 nm - Zhuang, Youyi; Mao, Wenjie; Gong, Xinghong; Jin, Xinxin; Li, Zhihong; Huang, Yidong; Duan, Yanmin (Frontiers in Physics, 2022)
Diode end-pumped Nd,La:CaNb2O6 self-Raman laser with acousto-optic Q-switching was successfully demonstrated for the first Stokes wave generation at 1,174 nm. A 1.0 at.% Nd3+ and 1.0 at.% La3+-doped CaNb2O6 crystal in dimensions 3 × 3 × 14.3 mm3 was used as the self-Raman laser crystal. Doping 1 at.% La3+ ions into this crystal could subdue the fluorescence quenching caused by cross-relaxation between Nd3+ ions and finally improve the laser output performance. Under the incident pump power of 9.9 W, the first Stokes wave at 1,174 nm with a maximum output power up to 928 mW was obtained, with the diode to Stokes conversion efficiency of about 9.4%. The results show that the Nd,La:CaNb2O6 is also a promising self-Raman crystal for efficient fundamental and Raman laser operation.